Preparation, Properties and Therapeutic Effect of a TPL Nanoparticle Thermosensitive Gel for Intra-Articular Injection - Lijuan Wang; Yongliang Ding; Qian Tang; Xiaodong Niu (Molecules, 2023)
Most injectable preparations for the articular cavity are solution-type preparations that are frequently administered because of rapid elimination. In this study, triptolide (TPL), an effective ingredient in the treatment of rheumatoid arthritis (RA), was prepared in the form of a nanoparticle thermosensitive gel (TPL-NS-Gel). The particle size distribution and gel structure were investigated by TEM, laser particle size analysis and laser capture microdissection. The effect of the nanoparticle carrier material PLGA on the phase transition temperature was investigated by 1H variable temperature NMR and DSC. The tissue distribution, pharmacokinetic behavior, four inflammatory factors and therapeutic effect were determined in a rat RA model. The results suggested that PLGA increased the gel phase transition temperature. The drug concentration of the TPL-NS-Gel group in joint tissues was higher than that in other tissues at different time points, and the retention time was longer than that of the TPL-NS group. After 24 days of administration, TPL-NS-Gel significantly improved the joint swelling and stiffness of the rat models, and the improvement degree was better than that of the TPL-NS group. TPL-NS-Gel significantly decreased the levels of hs-CRP, IL-1, IL-6 and TNF-α in serum and joint fluid. There was a significant difference between the TPL-NS-Gel and TPL-NS groups on Day 24 (p < 0.05). Pathological section results showed that inflammatory cell infiltration was lower in the TPL-NS-Gel group, and no other obvious histological changes were observed. Upon articular injection, the TPL-NS-Gel prolonged drug release, reduced the drug concentration outside the articular tissue and improved the therapeutic effect in a rat RA model. The TPL-NS-Gel can be used as a new type of sustained-release preparation for articular injection.